THE LEVEL OF CONTAMINATION OF COLIFORM BACTERIA IN PORK AT TRADITIONAL MARKETS KUTA SELATAN SUB-DISTRICT BADUNG REGENCY - Deasy Pitriyawati, Ni Kadek; Ngurah Swacita, Ida Bagus; Dary Mufa, Romy Muhammad (Buletin Veteriner Udayana, 2022)
The cleanliness of pork stalls in traditional markets can affect the microbial contamination of pork that sold in these markets. The purpose of this study was to determine the level of Coliform bacteria contamination in pork sold in the traditional market of South Kuta. The number of samples used in this study were 23 samples of pork 100 grams each taken from several traditional markets in South Kuta, Badung Regency to be tested for the amount of Coliform bacterial contamination by pouring method using Eosine Methylene Blue Agar (EMBA) media. Data on the level of Coliform bacteria contamination in pork were analyzed descriptively and displayed in the form of tables or graphs. The results showed that there was Coliform bacteria in the pork samples sold in the traditional market of South Kuta. It can be concluded that 95,65% (22/23) were in accordance with SNI Number 7388:2009, while 4.35% (1/23) were contaminated above 100 cfu /g. It is recommended to improve sanitation and hygiene in these traditional markets.